Dosimetric characteristics of 3D-printed and epoxy-based materials for particle therapy phantoms - Brunner, Jacob; Langgartner, Lorenz; Danhel, Hannah; Birkfellner, Wolfgang; Richter, Christian; Wagenaar, Dirk; Stock, Markus; Georg, Dietmar; Knäusl, Barbara (Frontiers in Physics, 2024)
Objective 3D printing has seen use in many fields of imaging and radiation oncology, but applications in (anthropomorphic) phantoms, especially for particle therapy, are still lacking. The aim of this work was to characterize various available 3D printing methods and epoxy-based materials with the specific goal of identifying suitable tissue surrogates for dosimetry applications in particle therapy. Methods 3D-printed and epoxy-based mixtures of varying ratios combining epoxy resin, bone meal, and polyethylene powder were scanned in a single-energy computed tomography (CT), a dual-energy CT, and a µCT scanner. Their CT-predicted attenuation was compared to measurements in a 148.2 MeV proton and 284.7 MeV/u carbon ion beam. The sample homogeneity was evaluated in the respective CT images and in the carbon beam, additionally via widening of the Bragg peak. To assess long-term stability attenuation, size and weight measurements were repeated after 6–12 months. Results Four 3D-printed materials, acrylonitrile butadiene styrene polylactic acid, fused deposition modeling printed nylon, and selective laser sintering printed nylon, and various ratios of epoxy-based mixtures were found to be suitable tissue surrogates. The materials’ predicted stopping power ratio matched the measured stopping power ratio within 3% for all investigated CT machines and protocols, except for µCT scans employing cone beam CT technology. The heterogeneity of the suitable surrogate samples was adequate, with a maximum Bragg peak width increase of 11.5 ± 2.5%. The repeat measurements showed no signs of degradation after 6–12 months. Conclusion We identified surrogates for soft tissue and low- to medium-density bone among the investigated materials. This allows low-cost, adaptable phantoms to be built for quality assurance and end-to-end tests for particle therapy.